Aberration of miRNAs Expression in Leukocytes from Sporadic Amyotrophic Lateral Sclerosis - Chen, YongPing; Wei, QianQian; Chen, XuePing; Li, ChunYu; Cao, Bei; Ou, RuWei; Hadano, Shinji; Shang, Hui-Fang (Frontiers in Molecular Neuroscience, 2016)
Background: Accumulating evidence indicates that miRNAs play an important role in the development of amyotrophic lateral sclerosis (ALS). Most of previous studies on miRNA dysregulation in ALS focused on the alterative expression in ALS animal model or in limited samples from European patients with ALS. In the present study, the miRNA expression profiles were investigated in Chinese ALS patients to explore leukocytes miRNAs as a potential biomarker for the diagnosis of ALS. Methods: We analyzed the expression profiles of 1733 human mature miRNAs using microarray technology in leukocytes obtained from 5 patients with sporadic ALS (SALS) and 5 healthy controls. An independent group of 83 SALS patients, 24 Parkinson's disease (PD) patients and 61 controls was used for validation by real-time polymerase chain reaction assay. Area under the receiver operating characteristic curve (AUC) was used to evaluate diagnostic accuracy. In addition, target genes and signaling information of validated differential expression miRNAs were predicted using Bioinformatics. Results: Eleven miRNAs, including four over-expressed and seven under-expressed miRNAs detected in SALS patients compared to healthy controls were selected for validation. Four under-expressed microRNAs, including hsa-miR-183, hsa-miR-193b, hsa-miR-451, and hsa-miR-3935, were confirmed in validation stage by comparison of 83 SALS patients and 61 HCs. Moreover, we identified a miRNA panel (hsa-miR-183, hsa-miR-193b, hsa-miR-451, and hsa-miR-3935) having a high diagnostic accuracy of SALS (AUC 0.857 for the validation group). However, only hsa-miR-183 was significantly lower in SALS patients than that in PD patients and in HCs, while no differences were found between PD patients and HCs. By bioinformatics analysis, we obtained a large number of target genes and signaling information that are linked to neurodegeneration. Conclusion: This study provided evidence of abnormal miRNA expression patterns in the peripheral blood leukocytes of SALS patients. Leukocytes miRNAs provide a promising opportunity for detection of SALS. The specificity of under-expression of hsa-miR-183 in SALS needs to be confirmed by further miRNA studies on other neurodegenerative diseases.